On the efficient Te4+→Yb3+ cooperative energy transfer mechanism in tellurite glasses: A potential material for luminescent solar concentrators - Rufino Souza, Ana Kely; Langaro, Ana Paula; Silva, Junior Reis; Costa, Francine Bettio [UNESP]; Yukimitu, Keizo [UNESP]; Silos Moraes, João Carlos [UNESP]; Antonio de Oliveira Nunes, Luiz; Humberto da Cunha Andrade, Luis; Lima, Sandro Marcio (Elsevier, 2019)
Te4+/Yb3+ co-doped 80%TeO2–20%Li2O glasses (amounts in mol%) were prepared by the conventional melt-quenching method in an ambient atmosphere, in order to investigate their optical characteristics for application in solar cells. An efficient near-infrared down-conversion mechanism was observed in these samples, involving the emission of two near infrared photons (at around 978 nm) after the absorption of one photon in the ultraviolet-blue region. This effect occurred by means of a process of cooperative energy transfer (CET) from Te4+ to Yb3+ ions. The CET efficiency (ηCET) was calculated from radiative transitions (lifetime) and also by a new method, developed in this work, based on rate equations quantifying the non-radiative transitions (thermal effect) involved in the system. The two methods showed very good agreement, with ηCET between 82 and 100% obtained for the sample prepared using a higher Yb3+ concentration (4 mol%). The results suggested that these tellurite materials could have potential applications in improving the efficiency of silicon-based solar cells.
Keywords: Cooperative energy transfer; Down-conversion; Te4+ ions; Tellurite glass; Thermal lens effect; Yb3+ ions